The Patristic and Medieval Background to a Theology of the Environment - Haffner, Paul (Studia Bioethica, 2016)
The Christian theology of creation directly contributes to the solution of the ecological crisis, affirming the fundamental truth that visible creation is itself a divine gift, the ‘original gift,’ which creates a ‘space’ for personal communion. Effectively, a correct Christian ecological theology is found in the application of theology to creation. The term ‘ecology’ combines the two Greek words, ‘oikos’ (house) and ‘logos’ (word): the physical environment of human existence could be seen as a sort of ‘habitation’ for human life. Considering that the interior life of the Holy Trinity is a life of communion, the divine act of creation is the totally free production of partners who can share in that communion. In this way, it can be said that the divine communion has now found its ‘habitation’ in the created cosmos. For this reason, it is possible to speak of the cosmos as a place of personal communion.